Causes and prognosis of adults experiencing a first seizure in adulthood: A pilot cohort study conducted in five countries in Latin America - Carpio, Arturo; Salgado, Carla; DiCapua, Daniela; Fleury, Agnes; Suastegui, Roberto; Giagante, Brenda; Aguilera, Ledda; Quijada, Alonso; Nuñez, Lilia; Villanueva, Manuela; Plascencia-Alvarez, Noel; Hamamoto Filho, Pedro T [UNESP]; et al. (Wiley, 2024)
There are limited data on first seizure (FS) among adults in low and middle-income countries. We describe findings from a prospective cohort study involving 180 adults presenting with seizures in emergency departments in five Latin American countries. Overall, 102 participants (56.7%) had acute symptomatic seizures (ASyS) while 78 (43.3%) had unprovoked seizures (UPS). Among patients with ASyS, 55 (53.9%) had structural causes, with stroke (n = 24, 23.5%), tumor (n = 10, 9.8%), and trauma (n = 3, 3%) being the most frequent. Nineteen patients (18.6%) had infectious causes, including four (4%) with meningoencephalitis, three (3%) neurocysticercosis, and two (2%) bacterial meningoencephalitis. Twenty patients (19.6%) had metabolic/toxic evidence, including four (4%) with uremic encephalopathy, two (2%) hyponatremia, and three (3%) acute alcohol intoxication. Immune dysfunction was present in seven (7%) patients and neurodegenerative in two (2%). Among participants with UPS, 45 (57.7%) had unknown etiology, 24 (30.7%) had evidence of structural disorders (remote symptomatic), four (5%) were related to infectious etiology (>7 days before the seizure), and five (6.4%) had genetic causes. During the 3- and 6-month follow-up, 29.8% and 14% of patients with UPS, respectively, experienced seizure recurrence, while 23.9% and 24.5% of patients with ASyS had seizure recurrence. Longer follow-up is necessary to assess seizure recurrence for patients with ASyS after the acute cause is resolved and to determine the 10-year risk of recurrence, which is part of the definition of epilepsy. Plain Language Summary: We monitored 180 adults who presented with their first seizure in emergency departments across five Latin American countries. Among these patients, 57% had acute symptomatic seizures, with structural causes such as stroke (23%), infection (17%), or tumor (10%) being more prevalent. Among the 43% with unprovoked seizures, 58% showed no identifiable acute cause, while 6.4% were due to genetics. Within 3 months after their initial seizure, 26.6% of individuals experienced a second seizure, with 11.9% continuing to have seizures in Months 3–6. Between Months 3 and 6, an additional 20% of patients encountered a second seizure. Research is needed to better understand the cause and prognosis of these patients to improve outcomes.
Keywords: acute symptomatic seizures; epilepsy; etiology; first seizure; neurocysticercosis